Ecotoxicidade, segurança clínica e eficácia de fármacos em jovens de pacu (Piaractus mesopotamicus) - Carraschi, Silvia Patrícia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The therapeutics use in the fish disease treatment is a common practice, due at intensive management and pathogens appearance that can cause high mortality rate. The objectives were to evaluate four drugs: enrofloxacine (ENRO), toltrazuril (TOL); florfenicol (FFC) and thiamethoxan (TH) in the pathogens control in pacu (Piaractus mesopotamicus), to evaluate the hemathological and histopathological variables after treatment and to evaluate the toxicity these drugs for target organism Piaractus mesopotamicus and for bioindicators: mato grosso (Hyphessobrycon eques); Lemna minor; Pomacea canaliculata and Daphnia magna. The organisms were acclimated in room bioassay with controlled temperature according to standard to each one. They were exposed at nominal concentrations in static system. The efficacy of TOL in the Ichthyophthirius multifiliis, Trichodina heterodentata and Anacanthorus penilabiatus control and ENRO, of Aeromonas sp and Streptococcus sp was evaluated in micro and mesocosm condition. The efficacy of TH in the A. penilabiatus control was prospected in laboratory and microcosmo and associated with FFC, in Aeromonas sp e Streptococcus sp control, in mesocosm. After the efficacy in mesocosm the blood was collected for hemathology analysis and tissues for histopatology. FFC, ENRO and TH are few toxics and TOL, moderately toxic, because the biondicator L. minor was the end point for FFC; the snail, for ENRO and the mato grosso, for TOL and TH. TOL is effectiveness in I. multifiliis and T. heterodentata control, o TH in A. penilabiatus and ENRO and FFC, Aeromonas sp and Streptococcus sp. The drugs cause no hemathological and histophatological changes that compromises the development of fish, and they are potentials molecules to get the register in treatment of P. mesopotamicus

O uso de fármacos no tratamento de doenças dos animais de criação na aquicultura é uma prática comum, devido ao manejo intensivo e a ocorrência de patógenos que podem causar perdas na produtividade. Objetivou-se avaliar quatro fármacos, a enrofloxacina (ENRO), o toltrazuril (TOL); o florfenicol (FFC) e o thiamethoxan (TH) no controle de parasitos e bactérias em pacu (Piaractus mesopotamicus), avaliar as variáveis histológicas e hematológicas após o tratamento e avaliar a toxicidade destes fármacos para o organismo alvo Piaractus mesopotamicus e para os bioindicadores: mato grosso (Hyphessobrycon eques); Lemna minor; Pomacea canaliculata e Daphnia magna. Nos ensaios de toxicidade os organismos foram aclimatados em salas de bioensaio de acordo com as normas vigentes para cada organismo e foram expostos às concentrações nominais em sistema estático. A eficácia do TOL no controle de Ichthyophthirius multifiliis, Trichodina heterodentata e Anacanthorus penilabiatus e da ENRO, de Aeromonas sp e Streptococcus sp foi avaliada em micro e mesocosmo. A eficácia do TH no controle de A. penilabiatus foi prospectada em laboratório e microcosmo e associado ao FFC, no controle de Aeromonas sp e Streptococcus sp, em mesocosmo. Após a eficácia em mesocosmo foi coletado sangue, para a análise hematológica e tecidos, para análise histopatológica. O FFC, a ENRO e o TH são pouco tóxicos e o TOL, moderadamente tóxico, pois o biondicador L. minor foi o end point para o FFC; o caramujo, para a ENRO e o mato grosso, para o TOL e TH. O TOL é eficaz no controle de I. multifiliis e T. heterodentata, o TH, contra A. penilabiatus e a ENRO e o FFC, Aeromonas sp e Streptococcus sp. Os fármacos não causam alterações hematológicas e histopatológicas que comprometam o desempenho zootécnico dos animais, sendo moléculas potenciais para obter registro brasileiro no tratamento de P. mesopotamicus
Keywords: Peixe - Doenças; Pacu (Peixe); Quimioterapia; Indicadores (Biologia); Hematologia; Toxicologia; Fishes